(untitled) (Asian Education Studies, 2019)
Establishing the connection between the scientific experiment and theory may pose quite a challenge for learners. Analyzing and interpreting data, they collect in the experiments, helps to bridge the gap between the experiment’s results and the theoretical world. The present research examines the barriers pre-service physics teachers confront with when dealing with data analysis tasks in the introductory physics laboratory. Identifying pre-service physics teachers’ misconceptions is very important because the future teachers can transfer them to their students. The novelty of this research is not only in identifying the physics teacher’s trainee’s misconceptions analyzing data in the introductory physics laboratory, but also in explaining the reasons for them. 25 pre-service physics teachers who had undergone several laboratory courses participated in this study. For examining their knowledge level and identifying their difficulties in data analysis, the Laboratory Data Analysis Instrument (LDAI) was used. The results revealed that the participants evidenced a sixty-nine percent overall average of correct answers. The various misconceptions the pre-service physics teachers encountered in each of the instrument objectives are identified and discussed. Dealing with multiple representations and the use of intuitive rules can explain some of the difficulties. The identification of the data analysis difficulties can be employed by educators attempting to construct more efficient learning environments.